Examen especial a la cuenta inventarios en la empresa autosierra S. A de la ciudad de Ambato del periodo enero a junio del 2013 - Mora Serrano, Ximena de los Ángeles (2014)
The special examination to the Inventoryaccountin the company AUTOSIERRASA During the period January to June 2013,were executed with to strengthen the level of truth at owns this business and comply with a requirement in the National University of Loja, prior to choose the degree of Engineer in Accounting and Auditing CPA. It was possible to meet the goals set at the beginning of the project planning procedures efficiently implement the special examination. Audit program according to the results obtained in the evaluation of internal control system that helped determine the reasonableness of the merchandise inventory account which were presented in the report was designed. Finally the final report with findings containing the same conclusions and recommendations was developed. Finally the final report with findings containing the same conclusions and recommendations was developed. At the conclusion reached by means of the research is that the line of business cannot be fully taken without proper inventory control and therefore the resource available, it is recommended to maintain inventory control through turnover rates that reflect roles and expectations, based on past experience.